PEMBUATAN APLIKASI SISTEM INFORMASI PENGELOLAAN KOMUNITAS KARUTA BERBASIS WEBSITE - Jessica Henry; Ery Dewayani; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
The OKAKURA karuta community is a gathering place for Indonesians who are interested in the game. The karuta community has carried out and participated in activities such as karuta training, workshops, and inter-community tournaments. The Website-Based Karuta Community Management Information System Application was created to help Karuta community administrators manage internal data and community members view training results. The lack of management data in the Karuta community creates uncertainty among community members, resulting in ineffective training procedures and data redundancy. Furthermore, because exercise recording is still done manually, community members who are not present cannot view training histories. As a result, a Website-Based Karuta Community Management Information System Application was developed to aid in the recording and management of data as well as the search for training history. The System Development Life Cycle development method was used in the creation of this application (SDLC). The programming languages used are HTML, CSS, and PHP, with MySQL as the database and XAMPP as a local server, resulting in a website application that can assist Karuta community administrators in data processing and makes it easier for community members to view training history.